Update on bacterial blight of rice: Fourth International Conference on Bacterial Blight - Sundaram, Raman. M.; Chatterjee, Subhadeep; Oliva, Ricardo; Laha, Gouri Sankar; Vera Cruz, Casiana; Leach, Jan E.; Sonti, Ramesh V. (Springer, 2014)
Bacterial blight (BB) of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most serious production constraints of rice worldwide. Besides the economic importance of the disease, the rice-Xoo system serves as an excellent model for studying host-pathogen interactions because the genomes of both interacting partners are sequenced and there is considerable genetic variation in the host and pathogen. The Fourth International Conference on Bacterial Blight (4th ICBB) of Rice was held in Hyderabad, India on 2–4 December 2013, and was jointly organized by the Centre for Cellular and Molecular Biology (CCMB), Directorate of Rice Research (DRR) and the Society for the Advancement of Rice Research. The 200 attendees represented 60 different institutions comprising universities, research institutes, and seed companies. The three-day conference provided an ideal atmosphere to discuss the latest developments in epidemiology, bacteria-rice interactions, and molecular breeding aspects of this important disease.